FRI0164 Anti-pfdn5 antibody as a biomarker for uveitis in ankylosing spondylitis. (12th June 2018) - Kwon, O.C.; Lee, E.-J.; Chang, E.-J.; Seo, W.J.; Oh, J.S.; Hong, S.; Lee, C.-K.; Yoo, B.; Kim, Y.-G.
Abstract : Background: Noninfectious uveitis is the most common extra-articular manifestation of ankylosing spondylitis (AS). However, molecules related to the disease pathogenesis have yet to be identified, and no biomarkers are available for uveitis in AS. Objectives: We aimed to identify the biomarkers for uveitis in AS, and elucidate the possible pathogenesis of uveitis in AS associated with the identified biomarkers. Methods: Protein microarray using ProtoArray was performed to profile autoantibodies present in sera from patients with various autoimmune diseases, including eight AS patients with uveitis. The autoantibodies with higher reactivity in AS patients with uveitis compared with other patients were selected, and the levels of autoantibodies were measured using ELISA in the sera from AS patients with (n=32) or without uveitis history (n=32), patients with rheumatoid arthritis (n=20) and from healthy individuals (n=12). To evaluate the involvement of target antigen in pathogenesis of spondyloarthritis-related uveitis, we conducted an in vivo study using curdlan-induced SKG mice, which spontaneously develops arthritis as well as uveitis, and an in vitro study using retinal pigment epithelium cell-line (RPE19). Results: 4 antibodies (Abs) were selected as a candidate for biomarker (anti-PFDN5, area under curve [AUC]=1.00; anti-serine threonine protein kinase 24 Ab, AUC=0.906; anti-odontogenic ameloblast associated protein Ab, AUC=0.859; anti-protocadherin alpha C2 Ab, AUC=0.859). In ELISA, anti-PFDN5 Abs was significantly elevated in AS patients with uveitis compared to AS patients without uveitis. Ocular histology showed that compared to PBS-treated SKG mice, SKG mice with uveitis had strong expression of PFDN5 in iris, ciliary body, and retina. PERK and peIF2α, which are ER stress related proteins, were downregulated in PFDN5 siRNA-treated RPE19 cells in tunicamycin-induced condition, suggesting that PFDN5 enhances ER stress via PERK and peIF2α pathway. Conclusions: We identified anti-PFDN5 antibody as a putative biomarker for uveitis in AS. PFDN5 was increased in ocular lesion, which may be associated with disease pathogenesis. Acknowledgements: None. Disclosure of Interest: None declared